Understanding climate from the ground up: Knowledge of environmental changes in the East African Savannas - Galvin, K. A.; Even, T.; Reid, R.; Njoka, J.; Roque de Pinho, J.; Thornton, P.; Saylor, K. (Changing climate, changing worlds: Local knowledge and the challenges of social and ecological change, 2020)
Africa makes a relatively minor contribution to global greenhouse gas emissions compared with developed nations, yet the African continent will be increasingly vulnerable to climate change processes in the coming decades. Critical challenges include meeting basic needs for food, water, shelter, and other necessities without undermining biodiversity and ecosystem services. Coordination efforts to address multiple climate-related stressors have generally occurred at the national level and taken an external approach, with national governments favoring collaboration with foreign-based NGOs and other international institutions over working with lower levels of government. However, the involvement of actors at the local level correlates with decisions that are better adapted to local social-cultural and environmental contexts, reducing implementation costs and increasing trust, thereby increasing the equity and efficacy of decentralized approaches. This chapter examines indigenous and local knowledge of climate change. It addresses climate and environmental change from the perspectives of Kenyan pastoralists who identified a myriad of environmental issues that occur and interact at different scales. They also identified ways forward at several scales from the local to the global. The continued functioning of ecosystems by and for local populations will depend critically upon sound policy, planning, and practice.